The Effect of Cognitive Distraction on Saccadic Latency - Halliday, Jane; Carpenter, Roger H S (Perception (London), 2010)
Saccadic initiation is increasingly being studied as a surrogate for more general neural mechanisms of decision-making. Visual ‘decision-making’ is thought to be controlled by higher cortical functions. Lower areas such as the superior colliculus are thought to be involved with more primitive optomotor reflexes that can generate short-latency saccades. It is now well established that imposition of fronto-executive load on subjects performing a saccadic task which, in particular, involves suppression of saccades (the no-go saccadic task), increases the number of errors made. It is theorised that a weakening of cortical control of the superior colliculus is responsible for the increase in error rate. One way to test this theory is to measure the latency of incorrect saccades made in a no-go saccadic task in relation to error rate under different conditions of fronto-executive load. A high error rate combined with an increased number of short-latency saccades in the range of express or early saccades would indicate that subjects have an inability to inhibit these short-latency more reflexive saccades, which seem to originate in the superior colliculus. Hence the normal cortical control of the superior colliculus is weakened. We used a saccadic go/no-go task under fronto-executive load and found that the proportion of short-latency saccades increased with audio-verbal interference, in conjunction with an increase in error rate. These findings provide strong empirical evidence to support the theory that maintenance of cortical functions is key to the control of saccadic responses. Under conditions of fronto-executive loading such cortical control is weakened, leaving subjects with a reduced ability to inhibit short-latency more reflexive saccades.